Physical and psychological differences between athletes with and without chronic primary low back pain: a scoping review - Prunault, Clément; Vadez, Guillaume; Descarreaux, Martin; Abboud, Jacques (Frontiers in Sports and Active Living, 2025)
ObjectiveLow back pain among athletes varies by sport, age, and sex, affecting performance and contributing to sports retirement. Recently, there has been an increasing focus on chronic primary low back pain (CPLBP) in athletes. The aim of this scoping review is to examine the existing literature on CPLBP, focusing on the physical and psychological differences between athletes with and without CPLBP.Design and MethodsA systematic search across MEDLINE, CINAHL, SportDiscus, and PsycINFO, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guidelines (PRISMA), identified 11 relevant studies. Three key concepts guided the search: “chronic low back pain”, “physical and psychological characteristics”, and “athletes”.ResultsFrom 1,767 screened articles, 11 studies involving 717 athletes (301 with CPLBP and 416 without) met the inclusion criteria. Most studies showed that athletes with CPLBP had significantly lower trunk muscle activation amplitudes and delayed onset. One study found that athletes with CPLBP had significantly reduced trunk extension strength. Kinematic evaluations showed a significant increase in trunk damping and lumbar extension in athletes with CPLBP compared to athletes without CPLBP. However, other studies reported no significant differences in trunk muscle activity, kinetic and kinematic variables. Finally, athletes with CPLBP reported significantly higher kinesiophobia, anxiety and pain catastrophizing scores.ConclusionsThis review shows significant physiological and psychological differences between athletes with and without CPLBP. Future research should focus on sport-specific assessments of CPLBP and its impact on performance.